2020
DOI: 10.2147/oajsm.s251081
|View full text |Cite
|
Sign up to set email alerts
|

<p>Injury Analysis in Professional Soccer by Means of Media Reports – Only Severe Injury Types Show High Validity</p>

Abstract: Purpose Injury data of professional soccer players obtained from media reports are frequently used in scientific research, but the accuracy of such data is still unclear. Patients and Methods Injuries of professional soccer players of the German first and second league were documented by continuously screening media reports over one season (2015–2016). After the season, the validity of media-reported injuries was anonymously analyzed by the team physicians of 8 differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 26 publications
1
34
0
2
Order By: Relevance
“…Severe injuries showed an equal pattern and were well documented in media with rates between 73.3% for fractures and 100% for joint dislocations. Hence, this research found in football similar results in analysis of media [21]. Our study extends these previous findings to the popular team ball sports handball and basketball.…”
Section: Basketball Handballsupporting
confidence: 90%
See 2 more Smart Citations
“…Severe injuries showed an equal pattern and were well documented in media with rates between 73.3% for fractures and 100% for joint dislocations. Hence, this research found in football similar results in analysis of media [21]. Our study extends these previous findings to the popular team ball sports handball and basketball.…”
Section: Basketball Handballsupporting
confidence: 90%
“…Due to a lack of validation of this study protocol, this study aimed to identify the validity of injury surveillance based on media reports. Recently, first results of a media report analysis in professional football were published [ 21 ]. However, in other team sports data are missing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury data provided by medical staff and players as required for longitudinal studies are rarely available. Therefore, injury data for this study were prospectively documented in a standardised manner according to media analysis [ 14 , 15 , 22 , 23 , 27 ]. This analysis was mainly based upon data obtained from the German kicker ® sports magazine, which is published twice a week and represents one of the main media sources about the first Bundesliga in Germany.…”
Section: Methodsmentioning
confidence: 99%
“…Teams do not intend to share sensitive data with the media. However, the underlying methodological standards (media-based injury registries) have previously been used in injury research [3,4,[42][43][44]. The advantage is the massive increase in availability of media-based information [6,7,28,45,46].…”
Section: Methodological Considerationsmentioning
confidence: 99%